Composition for tissue repair treatment comprising active substance

KR103031223B1Active Publication Date: 2026-10-13CHAMEDITECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
KR1020230040655
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-03-28
Publication Date
2026-10-13
Estimated Expiration
2043-03-28

Smart Images

  • Figure 112023035043835-PAT00003_ABST
    Figure 112023035043835-PAT00003_ABST
Patent Text Reader

Abstract

The present invention relates to a tissue repair composition comprising: a copolymer having a structure of [Chemical Formula 1] or [Chemical Formula 2] as a binding structure; a mixture of glycerin and hyaluronic acid salt; and one or more active substances selected from astaxanthin, adenosine, and idebenone: [Chemical Formula 1] XY [Chemical Formula 2] XYX In the above [Chemical Formula 1] or [Chemical Formula 2], X is a hydrophilic biocompatible polymer, and Y is a hydrophobic biocompatible polymer.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a tissue repair composition comprising an active substance. Background Technology

[0002] Compositions for tissue repair are generally used for therapeutic purposes to rehydrate the skin by mesotherapy for cosmetic purposes, filling of biological tissues, or alternative purposes such as wrinkle peeling, facial remodeling, and lip volume increase.

[0003] Currently, various materials are being used for tissue repair. Among them, hyaluronic acid accounts for more than 90% of the global filler market. However, it has a very low duration of effect due to its half-life in the body being within 1 to 3 days and rapid reabsorption within the body, resulting in a lack of long-term sustained effect. Products are being sold that extend the reabsorption period by cross-linking hyaluronic acid with a cross-linking agent. However, in the case of these cross-linked products, the cross-linking agent BDDE (1,4-butanediol diglycidyl ether) is a toxic carcinogen, leading to problems such as increased processing costs due to the removal process, product disposal due to microbial contamination, and product disposal due to the detection of residues.

[0004] Accordingly, numerous tissue repair products utilizing biodegradable polymers have been developed. As for existing filler formulations using biocompatible polymers, formulations have been developed and used in which water-insoluble polymers are processed into micro-sized particles and dispersed using viscous excipients or thickeners. For example, formulations in which polylactic acid (PLA) particles are dispersed in an aqueous solution of carboxymethylcellulose (CMC) or polycaprolactone (PCL) particles are dispersed in an aqueous solution of CMC and glycerin have been used. However, these formulations have problems such as the inconvenience of the needle being clogged by the particles during injection and the inability to achieve a uniform tissue repair effect because the particles are not uniformly dispersed. Prior art literature

[65535] Republic of Korea Published Patent No. 10-2021-0063274 The problem to be solved

[0005] The present invention has been devised to solve the problems of the aforementioned prior art. The present invention aims to provide a tissue repair composition using a copolymer having nano-sized particles, which possesses various functions such as wrinkle improvement, whitening, and anti-aging, by including active substances in the micelle core of the copolymer. means of solving the problem

[0006] In order to solve the above problem, the present invention,

[0007] A tissue repair composition is provided comprising: a copolymer having a structure of [Chemical Formula 1] or [Chemical Formula 2] as a bonding structure; a mixture of glycerin and hyaluronic acid salt; and one or more active substances selected from astaxanthin, adenosine, and idebenone.

[0008] [Chemical Formula 1]

[0009] XY

[0010] [Chemical Formula 2]

[0011] XYX

[0012] In the above [Chemical Formula 1] or [Chemical Formula 2],

[0013] X is a hydrophilic biocompatible polymer, and Y is a hydrophobic biocompatible polymer.

[0014] According to the present invention, the hydrophilic biocompatible polymer may be one or more polymers selected from the group consisting of methoxypolyethylene glycol, dihydroxypolyethylene glycol, monoalkoxypolyethylene glycol, monoacylpolyethylene glycol, and polyethylene glycol.

[0015] According to the present invention, the average molecular weight of the hydrophilic biocompatible polymer may be 1500 to 2500 g / mol.

[0016] According to the present invention, the hydrophobic biocompatible polymer may be polycaprolactone (PCL).

[0017] According to the present invention, when the copolymer comprises the structure of [Chemical Formula 1] as the bonding structure, the average molecular weight of the hydrophobic biocompatible polymer is 1500 to 4500 g / mol, and when the copolymer comprises the structure of [Chemical Formula 2] as the bonding structure, the average molecular weight of the hydrophobic biocompatible polymer may be 8500 g / mol or less.

[0018] According to the present invention, when the copolymer comprises the structure of [Chemical Formula 2] as a bonding structure, the average molecular weight of the hydrophobic biocompatible polymer may be 7500 to 8500 g / mol.

[0019] According to the present invention, 0.5 to 1.5% (w / v) of glycerin may be included for every 10% (w / v) of the copolymer.

[0020] According to the present invention, the copolymer may contain 0.5 to 1.5% (w / v) of hyaluronic acid salt with respect to 10% (w / v).

[0021] According to the present invention, the copolymer may contain 0.05 to 1% (w / v) of an active substance for every 10% (w / v) of the copolymer.

[0022] According to the present invention, arginine may be further included. In this case, 0.05 to 1% (w / v) of arginine may be included with respect to 10% (w / v) of the copolymer.

[0023] According to the present invention, the copolymer may comprise 0.05 to 0.15% (w / v) arginine, 0.5 to 1.5% (w / v) glycerin, 0.5 to 1.5% (w / v) hyaluronic acid, and 0.05 to 0.15% (w / v) active substance with respect to 10% (w / v) of the copolymer.

[0025] The present invention also provides a tissue repair injectable composition comprising the tissue repair composition.

[0027] The features and advantages of the present invention will become more apparent from the following detailed description based on the accompanying drawings.

[0028] Prior to this, terms and words used in this specification and claims shall not be interpreted in their ordinary and dictionary meanings, but must be interpreted in a meaning and concept consistent with the technical spirit of the invention, based on the principle that the inventor may appropriately define the concept of the terms to best describe his invention. Effects of the invention

[0029] According to the present invention, a tissue repair composition using a copolymer having nano-sized particles and various functions such as wrinkle improvement, whitening, and anti-aging is provided by including active substances in the micelle core of the copolymer. Brief explanation of the drawing

[0030] Figure 1 shows the results of measuring the particle size of the dipolymer mPEG (2,000)-PCL (4,500) used in the present invention. Figure 2 shows the results of measuring the particle size of the terpolymer mPEG (2,000)-PCL (8,000)-mPEG (2,000) used in the present invention. Figure 3 shows the results of measuring cytotoxicity according to molecular weight of the copolymer used in the present invention. Figure 4 shows the results of measuring the collagen-producing ability of the copolymer used in the present invention according to its molecular weight. Figure 5 shows the results of measuring the antioxidant capacity of the tissue repair composition of the present invention. Specific details for implementing the invention

[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by a skilled expert in the art to which this invention pertains. In general, the nomenclature used herein is well known and commonly used in the art.

[0033] The term 'composition' of the present invention is considered to include not only products containing specific components, but also any products made directly or indirectly by the combination of specific components.

[0034] In the present invention, the polymer molecular weight refers to the number average molecular weight (Mn). The number average molecular weight refers to the average molecular weight obtained by averaging the molecular weights of the constituent molecular species of a polymer compound having a molecular weight distribution by the moisture content or mole fraction.

[0035] The term "tissue repair" in this invention refers to a mechanism that restores tissue to its original state when necrosis, defects, etc., occur in skin tissue or the like due to causes such as trauma, inflammation, or aging.

[0036] The term 'biocompatibility' in the present invention refers to a characteristic in which a biomaterial must not exhibit a rejection reaction when in contact with biological tissues or body fluids, and does not exhibit cytotoxicity, irritation of biological tissues, induction of inflammation, induction of allergies, or thrombosis within the body. In other words, it refers to a characteristic in which it does not have a negative effect on normal metabolism and physiological processes through interaction with biological tissues.

[0037] In addition to these terms, other terms are defined elsewhere in the specification where necessary. Unless otherwise explicitly defined herein, industry terms used herein will have the meanings recognized in the industry.

[0039] Conventional tissue repair compositions using biocompatible polymers are formulations in which water-insoluble polymers are processed into micro-sized particles and dispersed using viscous excipients or thickeners. However, these formulations present problems such as the inconvenience of the needle clogging due to the particles during injection and the inability to achieve a uniform tissue repair effect because the particles are not uniformly dispersed.

[0040] The inventors have devised this invention to solve the problems of the aforementioned prior art. In this invention, active substances are incorporated into the micelle core of the copolymer, thereby providing a tissue repair composition using a copolymer having a nano-sized particle size while possessing various functions such as wrinkle improvement, whitening, and anti-aging of the skin.

[0041] To this end, the present invention provides a tissue repair composition comprising: a copolymer having a structure of [Chemical Formula 1] or [Chemical Formula 2] as a bonding structure; a mixture of glycerin and hyaluronic acid salt; and one or more active substances selected from astaxanthin, adenosine, and idebenone:

[0042] [Chemical Formula 1]

[0043] XY

[0044] [Chemical Formula 2]

[0045] XYX

[0046] In the above [Chemical Formula 1] or [Chemical Formula 2],

[0047] X is a hydrophilic biocompatible polymer, and Y is a hydrophobic biocompatible polymer.

[0048] When the copolymer of the present invention is introduced into the human body or applied to the skin, it can provide the effect of removing or alleviating wrinkles through the formation of natural tissue via collagen production.

[0049] At this time, the hydrophilic biocompatible polymer may be one or more polymers selected from the group consisting of methoxypolyethylene glycol, dihydroxypolyethylene glycol, monoalkoxypolyethylene glycol, monoacylpolyethylene glycol, and polyethylene glycol, and more preferably may be methoxypolyethylene glycol.

[0050] In addition, as can be seen from the results of the following examples, it is preferable that the average molecular weight of the hydrophilic biocompatible polymer be 1500 to 2500 g / mol. If the average molecular weight of the hydrophilic biocompatible polymer falls outside the above numerical range, there are problems such as poor solubility due to poor dissolution in an aqueous solution, unsuitability for use due to the size of the obtained particles being too large, and low collagen production ability.

[0051] In addition, the above hydrophobic biocompatible polymer is preferably polycaprolactone (PCL).

[0052] In addition, when the copolymer includes the structure of [Chemical Formula 1] as a bonding structure, it is preferable that the average molecular weight of the hydrophobic biocompatible polymer be 1500 to 4500 g / mol, and when the copolymer includes the structure of [Chemical Formula 2] as a bonding structure, it is preferable that the average molecular weight of the hydrophobic biocompatible polymer be 8500 g / mol or less, and more preferable that it be 7500 to 8500 g / mol. At this time, if the average molecular weight of the hydrophobic biocompatible polymer falls outside the above numerical range, there is a problem that the solubility may be reduced because it does not dissolve well in an aqueous solution, the size of the obtained particles may be too large and unsuitable for use, and the collagen production ability may be low.

[0054] In addition, the composition of the present invention may include a mixture of glycerin and hyaluronic acid salt. In this case, the glycerin is a water-soluble moisturizing ingredient that can provide excellent efficacy in moisturizing the skin, as well as provide an effect of improving the viscosity of the composition. In addition, the hyaluronate is a natural moisturizing ingredient and is used interchangeably with the sodium salt of hyaluronic acid or hyalonic acid. It has a moisture content of 6,000 times that of skin tissue, so it can provide elasticity to the skin and act as a protective barrier to prevent moisture from evaporating by forming a protective film on the skin, and this can also provide an effect of improving the viscosity of the composition.

[0055] The average molecular weight of the hyaluronic acid salt is preferably 5,000 to 800,000 Da, and more preferably 500,000 to 700,000 Da. At this time, if the molecular weight of the hyaluronic acid or its salt falls outside the above numerical range, there is a problem that it does not dissolve well in an aqueous solution and thus has reduced solubility.

[0056] In the composition according to the present invention, it is preferable to include 0.5 to 1.5% (w / v) of glycerin with respect to 10% (w / v) of the copolymer, and it is preferable to include 0.5 to 1.5% (w / v) of hyaluronic acid salt with respect to 10% (w / v) of the copolymer. For example, when the concentration of the copolymer is 10% (w / v), the concentration of glycerin and hyaluronic acid is preferably 0.5 to 1.5% (w / v); when the concentration of the copolymer is 5% (w / v), the concentration of glycerin and hyaluronic acid is preferably 0.25 to 0.75% (w / v); when the concentration of the copolymer is 15% (w / v), the concentration of glycerin and hyaluronic acid is preferably 0.75 to 2.25% (w / v); and when the concentration of the copolymer is 20% (w / v), the concentration of glycerin and hyaluronic acid is preferably 1 to 3% (w / v). At this time, if the content of the glycerin and hyaluronic acid salts falls outside the above numerical range, there is a problem that the viscosity increase effect is minimal or the viscosity increases significantly, showing gel-like properties, making it unsuitable for use.

[0058] In addition, the composition of the present invention may include one or more active substances selected from astaxanthin, adenosine, and idebenone. The active substances included in the composition of the present invention can exhibit effects such as antioxidant capacity, wrinkle improvement, whitening, and prevention of skin aging. In the composition according to the present invention, it is preferable to include 0.05 to 1% (w / v) of the active substance with respect to 10% (w / v) of the copolymer, and it is more preferable to include 0.05 to 0.15% (w / v). At this time, if the content of the active substance falls outside the above numerical range, there is a problem that the effect of the active substance is negligible, or that it is not easily dissolved in an aqueous solution, resulting in reduced solubility and making it unsuitable for use.

[0060] In addition, the composition of the present invention may further include arginine. The arginine can exhibit an anti-aging effect on the skin through antioxidant action and can adjust the pH of an acidic copolymer colloid aqueous solution included in the composition of the present invention to a weakly acidic state. In the composition according to the present invention, it is preferable to include 0.05 to 1% (w / v) of arginine with respect to 10% (w / v) of the copolymer, and it is more preferable to include 0.05 to 0.15% (w / v).

[0062] In addition, in the composition according to the present invention, it is most preferable to include 0.05 to 0.15% (w / v) of arginine, 0.5 to 1.5% (w / v) of glycerin, 0.5 to 1.5% (w / v) of hyaluronic acid, and 0.05 to 0.15% (w / v) of an active substance with respect to 10% (w / v) of the copolymer. Through the following examples, it was confirmed that a composition satisfying the above content range has a particle size of about 300 nm or less than 300 nm and is uniformly dispersed in an aqueous solution, possesses excellent tissue repair ability such as collagen production, has pH and viscosity characteristics suitable for application in tissue repair compositions, and can exhibit effects such as antioxidant ability, wrinkle improvement, whitening, and anti-aging of the skin without skin irritation.

[0064] The present invention also provides a tissue repair injectable composition comprising the tissue repair composition.

[0065] The tissue repair injectable composition of the present invention may include a pharmaceutically acceptable injectable carrier. In this case, the carrier may be any ordinary material without limitation and may be selected from the group consisting of, for example, injectable distilled water, physiological saline, 5% glucose, buffer (e.g., phosphate buffer (PBS)), and combinations thereof, but is not limited thereto.

[0066] The tissue repair injectable composition of the present invention may further include one or more conventional additives usable in injectable formulations in addition to the above-mentioned components.

[0068] The present invention also provides a cosmetic composition comprising the tissue repair composition.

[0070] [Example]

[0071] The present invention will be described in more detail below through examples. These examples are solely for illustrating the present invention, and it will be obvious to those skilled in the art that the scope of the present invention is not to be interpreted as being limited by these examples. Accordingly, the actual scope of the present invention is defined by the appended claims and their equivalents.

[0073] Derivation of copolymer type and optimal molecular weight

[0074] Methoxypolyethylene glycol (mPEG) and ε-caprolactone were polymerized under a catalyst to obtain a methoxypolyethylene glycol-polycaprolactone copolymer (mPEG-PCL). The molecular weight of the prepared copolymer was confirmed using GPC (Gel permeation chromatography, Model: Waters e2695).

[0075] In addition, hexamethylene diisocyanate was added to a methoxypolyethylene glycol-polycaprolactone copolymer (mPEG-PCL) and reacted in the presence of a catalyst to obtain a methoxypolyethylene glycol-polycaprolactone-methoxypolyethylene glycol terpolymer (mPEG-PCL-mPEG). The molecular weight of the prepared copolymer was confirmed using GPC (Gel permeation chromatography, Model: Waters e2695).

[0076] Next, the yield according to the molecular weight of mPEG and PCL used in the preparation of the above dipolymer or terpolymer was measured and is shown in Table 1 below.

[0077] Copolymer molecular weight yield mPEG(2,000)-PCL(1,000) 96 mPEG(2,000)- PCL(2,000) 98 mPEG(2,000)- PCL(4,000) 99 mPEG(2,000)- PCL(6,000) 99 mPEG(2,000)- PCL(8,000) 99 mPEG(2,000)- PCL(10,000) 99 mPEG(5,000)- PCL(2,500) 96 mPEG(5,000)- PCL(3,500) 96 mPEG(5,000)- PCL(5,000) 96 mPEG(5,000)- PCL(7,500) 99 mPEG(5,000)- PCL(10,000) 99 mPEG(5,000)- PCL(12,500) 98 mPEG(5,000)- PCL(15,000) 98 mPEG(2,000)- PCL(8,000)- mPEG(2,000) 88 mPEG(2,000)- PCL(9,000)- mPEG(2,000) 80 mPEG(2,000)- PCL(10,000)- mPEG(2,000) 82

[0078] As shown in Table 1 above, it was confirmed that a yield of approximately 80% or more was achieved regardless of the molecular weight of mPEG and PCL.

[0080] Next, the copolymers prepared according to Table 1 above were stirred in an aqueous solution at a concentration of about 10 to 20 wt% at 80°C to 100°C for 1 to 3 hours to prepare a colloidal aqueous solution, and their solubility and particle size were measured and shown in Table 2 below. At this time, the particle size was measured using a nano particle size analyzer (Model: Sympatec NANOPHOX), and the particle sizes of the dipolymer mPEG(2,000)-PCL(4,000) and the tripolymer mPEG(2,000)-PCL(8,000)-mPEG(2,000) are shown in Figures 1 and 2 below, respectively.

[0081] Copolymer molecular weight Availability density(%) Particle size (nm) mPEG(2,000)- PCL(1,000) O 20 5.5 μm 10 8.7 μm mPEG(2,000)- PCL(2,000) O 10 446 nm mPEG(2,000)- PCL(4,000) O 10 96 nm 20 115 nm mPEG(2,000)- PCL(6,000) O 20 12 μm mPEG(2,000)- PCL(8,000) O 20 16 μm mPEG(2,000)- PCL(10,000) X - - mPEG(5,000)- PCL(2,500) O 10 7 μm mPEG(5,000)-PCL(5,000) O 10 6 μm mPEG(5,000)- PCL(7,500) O 10 11 μm mPEG(5,000)- PCL(10,000) O 10 11 μm mPEG(5,000)- PCL(12,500) X - - mPEG(5,000)- PCL(15,000) X - - mPEG(2,000)- PCL(8,000)- mPEG(2,000) O 10 200 nm mPEG(2,000)- PCL(8,000)- mPEG(2,000) O 20 179 nm mPEG(2,000)- PCL(9,000)- mPEG(2,000) X - - mPEG(2,000)- PCL(10,000)- mPEG(2,000) X - -

[0082] As shown in Table 2 above, in the case of the mPEG-PCL dipolymer, at a content of 10 to 20 weight%, when the molecular weight of mPEG is 1500 to 2500 g / mol (specifically 2000 g / mol) and the molecular weight of PCL is 1500 to 4500 g / mol (specifically 2000, 4000 g / mol), it is homogeneously dispersed in an aqueous solution with a particle size of 96 to 446 nm, whereas when the molecular weight of PCL is less than 1500 g / mol or exceeds 4500 g / mol, it was confirmed that the solubility is reduced or the particle size is too large, making it unsuitable. In addition, in the case of the mPEG-PCL-mPEG terpolymer, it was confirmed that when the molecular weight of mPEG is 1500 to 2500 g / mol (specifically 2000 g / mol) and the molecular weight of PCL is 8500 g / mol or less, 7500 to 8500 g / mol (specifically 8000 g / mol), it is homogeneously dispersed in an aqueous solution with a particle size of about 179 to 200 nm (Figs. 1 and 2).

[0084] mPEG- PCL Dipolymer and mPEG- PCL -mPEG of the terpolymer Measurement of cell viability and collagen production ability according to molecular weight

[0085] Cell viability and collagen production (PICP assay) according to molecular weight were measured using colloidal aqueous solutions of mPEG-PCL dipolymer and mPEG-PCL-mPEG terpolymer.

[0086] Measurement of cell viability

[0087] HDF cells were cultured in DMEM containing 10% FBS and 1% penicillin / streptomycin (GIBCO Thermo Fisher Scientific, Waltham, MA, USA). Cells were cultured in a 5% CO2 incubator maintained at 37°C. HDF cells were placed in a 48-well plate at a density of 1 x 10⁶ cells per well. 4Cells were seeded and cultured for 24 hours. Each sample was diluted to various concentrations in serum-free media and treated with the cells for 24 hours. After 24 hours of culture, the culture medium from each well was collected and used for the collagen synthesis assay below. 200 μL of fresh medium was added to each well, along with 20 μL of EZ-Cytox (DoGenBio, Korea) solution. The mixture was reacted for 4 hours, after which the absorbance was measured at an OD of 450 nm. The results of the cell viability measurement are shown in Figure 3 below. At this time, the mPEG-PCL dipolymer used mPEG(2,000)-PCL(2,000), mPEG(2,000)-PCL(4,000), and mPEG(5,000)-PCL(10,000), and the mPEG-PCL-mPEG terpolymer used mPEG(2,000)-PCL(8,000)-mPEG(2,000).

[0088] Through the results of Figure 3 below, it was confirmed that the copolymers used in the present invention are not cytotoxic regardless of their type and molecular weight.

[0090] Measurement of collagen production

[0091] The amount of newly generated collagen was measured using a Human Pro-Collagen I alpha 1 DuoSet ELISA (R&D, Korea). A 96-well plate was coated with Pro-Collagen I alpha 1 Capture Antibody, and 100 μL of culture medium sample or standard (Human Pro-Collagen I alpha 1 Standard) was added and incubated at room temperature for 2 hours. After washing, 100 μL of Pro-Collagen I alpha 1 Detection Antibody was added and incubated for an additional 2 hours. After washing twice, 100 μL of Streptavidin-HRP was added and incubated for 20 minutes, followed by the addition of 100 μL of the final HRP substrate solution and incubation for an additional 20 minutes. Subsequently, 50 μL of stop solution was added to each well, and the absorbance was measured at 450 nm. The results of the collagen production measurement are shown in Figure 4 below. At this time, the mPEG-PCL dipolymer used mPEG(2,000)-PCL(2,000), mPEG(2,000)-PCL(4,000), and mPEG(5,000)-PCL(10,000), and the mPEG-PCL-mPEG terpolymer used mPEG(2,000)-PCL(8,000)-mPEG(2,000).

[0092] Through the results shown in Figure 4 below, it was confirmed that all copolymers used had excellent collagen-generating ability. Among the copolymers, mPEG(2,000)-PCL(2,000) and mPEG(2,000)-PCL(4,000) showed excellent collagen-generating ability across all concentration ranges. In particular, it was confirmed that the mPEG(2,000)-PCL(4,000) copolymer had significantly improved collagen-generating ability across all concentration ranges (313, 1250, 5000 ppm). Additionally, it was confirmed that the mPEG(2,000)-PCL(8,000)-mPEG(2,000) tripolymer had significantly improved collagen-generating ability across all concentration ranges (313, 1250, 5000 ppm) compared to the mPEG-PCL copolymer.

[0094] Preparation of a tissue repair composition

[0095] In Arginine pH regulation by

[0096] The colloidal aqueous solution of the terpolymer mPEG(2,000)-PCL(8,000)-mPEG(2,000) has an acidic pH. Arginine was added to adjust the pH to a weakly acidic level of approximately 4.5 to 6.5, and an experiment was conducted to determine the optimal content. The results are shown in Table 3 below. At this time, the components of Table 3 were stirred in an aqueous solution at 80°C to 100°C for 1 to 3 hours.

[0097] PCL Tri-block* (%) Water (%) Arginine (%) pH 10 90% - 3.5 20 80% - 3.25 10 89.9 0.1 6.1 20 79.8 0.2 5.25

[0098] * PCL Tri-block: mPEG(2000)-PCL(8000)-mPEG(2000)

[0099] As shown in Table 3 above, it was confirmed that the pH of the composition becomes slightly acidic due to the addition of arginine, and specifically, it was confirmed that the pH can be adjusted to about 6.1 when the concentration of arginine is 0.1% (w / v) relative to 10% (w / v) of the copolymer, and to about 5.25 when the concentration of arginine is 0.2% (w / v) relative to 20% (w / v) of the copolymer.

[0101] Viscosity control by glycerin and HA

[0102] The colloidal aqueous solution of the terpolymer mPEG(2,000)-PCL(8,000)-mPEG(2,000) has a very low viscosity, making it difficult to use as a tissue repair composition. Therefore, the viscosity of the composition was improved using glycerin and hyaluronic acid salts. Experiments were conducted to determine the optimal content of these ingredients, and the results are shown in Table 4 below. During this process, the components listed in Table 4 were stirred in an aqueous solution at 80°C to 100°C for 1 to 3 hours. Additionally, hyaluronic acid salts with an average molecular weight of approximately 500,000 to 700,000 Da were used, and viscosity was measured using a viscometer (Brookfield, DV-III). + It was measured using , S02).

[0103] PCL Tri-block* (%) Arginine (%) Glycerin (%) Hyaluronate (%) viscosity 10 0.1 - - 28.8 10 0.1 1 - 79.2 10 0.1 2 - 128.1 20 0.2 1 - 198.3 10 0.1 1 1 416.8 10 0.1 1 3 Gel form

[0104] As shown in Table 4 above, it was confirmed that the viscosity of the composition increases when glycerin or hyaluronic acid is used, and in particular, it was confirmed that the viscosity improvement effect is further enhanced when glycerin and hyaluronic acid are mixed. In addition, when 1% glycerin (w / v) and 3% hyaluronic acid (w / v) are mixed with 10% (w / v) copolymer, the viscosity increases excessively and exhibits gel-like properties, whereas when 1% glycerin (w / v) and 1% hyaluronic acid (w / v) are mixed, the viscosity improvement effect is the best.

[0106] A tissue repair composition containing an active substance Antioxidant capacity

[0107] As shown in Table 5 below, a composition was prepared by adding 0.1% (w / v) arginine, 1% (w / v) glycerin, and 1% (w / v) hyaluronic acid to 10% (w / v) of the tripolymer mPEG(2,000)-PCL(8,000)-mPEG(2,000), and adding 0.1% (w / v) each of astaxanthin, adenosine, and idebenone as active substances, and stirring at 80°C to 100°C for 1 to 3 hours. The antioxidant capacity of the composition was measured, and the results are shown in Figure 5. At this time, the composition without added active substances was designated as the control, the composition with added astaxanthin was designated as Sample 1, the composition with added adenosine as Sample 2, and the composition with added idebenone as Sample 3.

[0108] PCL Tri-block* (%) Arginine (%) Glycerin (%) Hyaluronate (%) Active substance (%) 10 0.1 1 1 - 10 0.1 1 1 Astananthin0.1 10 0.1 1 1 Adenosine 0.1 10 0.1 1 1 Idebenone0.1

[0109] Through the results of Figure 5 below, it was confirmed that when the active substance according to the present invention is included, significantly improved antioxidant capacity is exhibited compared to the control group without the addition of the active substance.

[0111] Human skin primary irritation test

[0112] As shown in Table 5 above, a composition was prepared by adding 0.1% (w / v) arginine, 1% (w / v) glycerin, and 1% (w / v) hyaluronic acid to 10% (w / v) of the tripolymer mPEG (2,000)-PCL (8,000)-mPEG (2,000), and adding 0.1% (w / v) each of astaxanthin, adenosine, and idebenone as active substances, and stirring at 80°C to 100°C for 1 to 3 hours, and a primary skin irritation test was measured for these compositions. Specifically, the above compositions were submitted to the Skinmed Clinical Trial Center, and a final of 30 healthy adults aged 20 to 60 years without skin diseases or skin allergies were recruited to perform a skin irritation test on the back. Table 6 below classifies skin reactions according to the standards of Forsch & Klingman, the CTFA guideline, and the ICDRG (International Contact Dermatitis Research Group).

[0113] mark rating standard - 0.0 Unresponsive ± 0.5 Slight erythema, spotty or diffuse + 1 Moderate uniform erythema ++ 2 Intense erythema with edema +++ 3 Intense vesicles Calculation of skin reactivity Skin reactivity = Final Judgment Criteria Average skin reactivity verdict 0.0 - 0.9 Low stimulation 1.0 - 2.9 Gyeongja-geuk 3.0 - 4.9 Medium stimulation 5.0 or higher Strong stimulation

[0114] The overall procedure for the skin irritation test was conducted as shown in Table 7 below. Specifically, 20 μL of each of the four Formulation test products was applied to an IQ Ultra patch, attached to the back, and secured with 3M Micropore Tape. The test involved evaluating the skin irritation index visually and taking photographs. The first assessment was made 24 hours after patch application and 1 hour after removal, while the second assessment was made 24 hours after patch removal. The measurement results are shown in Table 8 below.

[0115] division Visit 1 Visit 2 Visit 3 Screening / Patch Application 1 hour after patch removal 24 hours after patch removal Test Subject Consent Form √ Review of Selection / Exclusion Criteria √ Medical history and concomitant drug investigation √ √ √ Screening number assignment √ Attach the patch √ Remove patch √ Expert visual inspection and photography √ √ Check for adverse reactions √ √

[0116] Test product control group Number of responders First reading Second reading Average skin reactivity verdict ± 1+ 2+ 3+ ± 1+ 2+ 3+ 1 1 0 0 0 0 0 0 0 0.28 Low stimulation Test product Sample 1 Number of responders First reading Second reading Average skin reactivity verdict ± 1+ 2+ 3+ ± 1+ 2+ 3+ 1 0 0 0 0 0 0 0 0 0.00 Low (non)irritating Test product Sample 2 Number of responders First reading Second reading Average skin reactivity verdict ± 1+ 2+ 3+ ± 1+ 2+ 3+ 1 0 0 0 0 0 0 0 0 0.00 Low (non)irritating Test product Sample 3 Number of responders First reading Second reading Average skin reactivity verdict ± 1+ 2+ 3+ ± 1+ 2+ 3+ 1 0 0 0 0 0 0 0 0 0.00 Low (non)irritating

[0117] As shown in Table 8 above, the compositions of the present invention were measured to have low skin irritation regardless of whether they contained an active substance, and in particular, compared to the control group without added active substances, when the active substance according to the present invention was included, the average skin reactivity was significantly lower, confirming that the skin irritation was lower.

[0119] Foregoing, specific parts of the present invention have been described in detail. It will be apparent to those skilled in the art that such specific descriptions are merely preferred embodiments and do not limit the scope of the invention. Accordingly, the actual scope of the invention is defined by the appended claims and their equivalents.

Claims

Claim 1 A copolymer comprising the structure of [Chemical Formula 1] or [Chemical Formula 2] as a bonding structure; a mixture of glycerin and hyaluronic acid salt; A tissue repair composition comprising [Chemical Formula 1]XY[Chemical Formula 2]XYX, wherein, in [Chemical Formula 1] or [Chemical Formula 2], X is a hydrophilic biocompatible polymer and Y is a hydrophobic biocompatible polymer, wherein the hydrophilic biocompatible polymer is methoxypolyethylene glycol with a number average molecular weight of 1500 to 2500 g / mol and is a copolymer having the structure of [Chemical Formula 1] as a bonding structure, the hydrophobic biocompatible polymer is polycaprolactone with a number average molecular weight of 1500 to 4500 g / mol and is a copolymer having the structure of [Chemical Formula 2] as a bonding structure, and the hydrophobic biocompatible polymer is polycaprolactone with a number average molecular weight of 7500 to 8500 g / mol. Claim 2 delete Claim 3 delete Claim 4 delete Claim 5 delete Claim 6 delete Claim 7 A tissue repair composition according to claim 1, characterized by containing 0.5 to 1.5% (w / v) of glycerin relative to 10% (w / v) of the copolymer. Claim 8 A tissue repair composition according to claim 1, characterized by containing 0.5 to 1.5% (w / v) of hyaluronic acid salt relative to 10% (w / v) of the copolymer. Claim 9 A tissue repair composition according to claim 1, characterized by containing 0.05 to 1% (w / v) of an active substance with respect to 10% (w / v) of the copolymer. Claim 10 A tissue repair composition according to claim 1, further comprising arginine. Claim 11 A tissue repair composition according to claim 10, characterized by containing 0.05 to 1% (w / v) of arginine with respect to 10% (w / v) of the copolymer. Claim 12 A tissue repair composition according to claim 10, characterized by comprising 0.05 to 0.15% (w / v) arginine, 0.5 to 1.5% (w / v) glycerin, 0.5 to 1.5% (w / v) hyaluronic acid, and 0.05 to 0.15% (w / v) active substance with respect to 10% (w / v) of the copolymer. Claim 13 A tissue repair injectable composition comprising a tissue repair composition according to claim 1.

Citation Information

Patent Citations

  • In-situ cross-linked integrated alginate graft

    JP2011509724A

  • Powder preparation for tissue repair treatment and method for preparing the same, and injection composition for tissue repair treatment comprising the same

    KR1020230014665A

  • Gel containing hyaluronic acid-polydeoxyribonucleotide copolymer and application thereof

    CN115192771A

  • Dermal Filler Composition Containing Polycaprolactone And Hyaluronic Acid

    KR1020170123099A

  • Composition for tissue repair treatment

    KR1020210063274A